Enhanced catalytic activity and stability of composite of cellulose film and nano zero-valent iron on Juncus effusus for activating peroxydisulfate to degrade Rhodamine B dye - Zhang, Shengli (Water science and technology : a journal of the International Association on Water Pollution Research, 2023)
In this study, a novel peroxydisulfate (PDS) activator (CF-nZVI-JE) was prepared via in-situ loading nano zero-valent iron (nZVI) on Juncus effusus (JE) followed with wrapping a layer of cellulose film (CF). The CF-nZVI-JE had the same 3D structure as the JE, being easy to separate from aqueous solution. The loaded nZVI existed single nanoparticles with a size of 60-100 nm except chain-type agglomeration of nanoparticles due to the stabilization of JE fibers. The activation performance of the CF-nZVI-JE for PDS was evaluated with Rhodamine B (Rh B) as a representative pollutant. Under the optimal activating conditions, the degradation rate of Rh B reached 99% within 30 min in the CF-nZVI-JE/PDS system. After five cycles, the degradation rate of Rh B was still over 85%, suggesting that the CF-nZVI-JE had good reusability. More interestingly, SO4·- and ·OH radicals were simultaneously detected in the CF-nZVI-JE/PDS system, but only SO4·- existed in the JE-ZVI/PDS system, suggesting the different activation mechanism. Meanwhile, the introduction of CF not only facilitated to the mineralization of Rh B but also significantly reduced the release amount of iron ions. Hence, the CF-nZVI-JE can be employed as a promising PDS activator for the treatment of organic wastewater